1999
DOI: 10.1177/135245859900500206
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 mRNA expression in blood and CSF mononuclear cells is augmented in multiple sclerosis

Abstract: Myelin-directed autoimmunity is considered to play a key role in the pathogenesis of multiple sclerosis (MS). Increased production of both pro- and anti-inflammatory cytokines is a common finding in MS. Interleukin-17 (IL-17) is a recently described cytokine produced in humans almost exclusively by activated memory T cells, which can induce the production of proinflammatory cytokines and chemokines from parenchymal cells and macrophages. In situ hybridisation with synthetic oligonucleotide probes was adopted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
359
0
9

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 660 publications
(390 citation statements)
references
References 23 publications
19
359
0
9
Order By: Relevance
“…Recent studies have shown that pathogenic IL-23-driven IL-17-producing cells can invade the CNS and promote the development of chronic CNS inflammation associated with autoimmunity (21). Indeed, microarray analysis demonstrated IL-17 expression in the plaques of MS brains (22) and increased IL-17-expressing mononuclear cells present in the cerebrospinal fluid of MS patients (21). Using bone marrow chimeric mice in which the p40 subunit common to IL-12 and IL-23 was absent in the CNS, it was shown that IL-23 produced by resident microglia and infiltrating macrophages in the CNS was critical to the clinical onset of EAE, but not for chronic CNS inflammation, suggesting that IL-23R engagement in the CNS was critical to the pathogenicity of infiltrating myelinspecific T cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that pathogenic IL-23-driven IL-17-producing cells can invade the CNS and promote the development of chronic CNS inflammation associated with autoimmunity (21). Indeed, microarray analysis demonstrated IL-17 expression in the plaques of MS brains (22) and increased IL-17-expressing mononuclear cells present in the cerebrospinal fluid of MS patients (21). Using bone marrow chimeric mice in which the p40 subunit common to IL-12 and IL-23 was absent in the CNS, it was shown that IL-23 produced by resident microglia and infiltrating macrophages in the CNS was critical to the clinical onset of EAE, but not for chronic CNS inflammation, suggesting that IL-23R engagement in the CNS was critical to the pathogenicity of infiltrating myelinspecific T cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…It was initially reported that IL-17 could be secreted by human CD4 1 T cells [15] and that IL-17 mRNA was elevated in the CSF and blood of patients with MS [16]. It was later demonstrated that IL-17-producing T cells were a distinct linage from Th1 or Th2 cells [17][18][19].…”
Section: T-cell Subtypes That Secrete Il-17mentioning
confidence: 99%
“…Increased levels of IL-17 were reported to correlate with disease intensity in allergic lung inflammation as observed in OVA-sensitized mice [12], in peritoneal inflammation after infection with Bacteroides fragilis [13], in rheumatoid arthritis [14], in multiple sclerosis [15] and in psoriasis [16].…”
Section: Introductionmentioning
confidence: 99%